Clinical, Endoscopic, and Histopathological Characteristics of Gastrointestinal Polyps - Sabhita Shabir Shaikh; Hafeezullah Shaikh; Syed Ahsan Ali; Rahila Khalid; Alveena Shabbir; Badder Hina Afnan (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Gastrointestinal polyps are common findings in endoscopy, leading to substantial morbidity and mortality. Unlike the West, screening programs for the early detection of polyps are not adopted in Pakistan. This study aims to define the characteristics of the polyps in our population that will encourage clinicians to follow screening and surveillance programs for the detection of polyps.METHODOLOGY: A prospective observational study. Patients who had polyps during endoscopy were enrolled. Clinical symptoms, endoscopic appearance and histopathology were noted. Patients refusing biopsy, polypectomy, or synchronous/ metachronous lesions were excluded.RESULTS: A total of 149 patients were enrolled, out of which 84 (56.4%) were males, and most of the gastrointestinal polyps were located in the colon 75(50.3%) and rectum 51(34.2%), respectively. 12(8.1%) patients had a family history of polyps/ GI malignancy, and 45(30.2%) had two or more polyps. 46(30.8%) patients had adenomatous polyps, all located in the colorectal region, and of these, 3 had high-grade dysplasia. Patients with adenomatous polyps had significantly higher age at presentation (mean±SD 1.02±15.66, p-value=0.007), a higher proportion of presence of alarm features including anemia 10(21.7%) with p-value=0.047, weight loss 22(47.8%) with p-value=0.003 and history of colorectal polyps/malignancy 8(17.4%) with p-value=0.009 compared to those patients who had non-adenomatous polyps.CONCLUSION: Upper GI tract polyps are mostly benign. Patients with adenomatous polyps are older, anemic at presentation, with a positive family history of colorectal polyps, and mostly found in the colorectum. Large multicenter studies are needed to predict the burden of polyps in our country in order to formulate national guidelines for screening and surveillance of colonoscopy in our country.